Codes of Ethics and Museum Research. Issue 1 (27th May 2014) - Bounia, Alexandra
This paper aims to focus on museum codes of ethics and discuss their provisions on museum research. Museum research is an important part of museum work; it is an ethical responsibility of museum professionals to perform this work for society and to encourage this undertaking in their institutions by other stakeholders. But how do codes of ethics in their current form encourage that? Instead of promoting a contemporary idea of research – multi-faceted, complex, open to the participation of many different interested parties, such as different professionals and communities of knowledge – they seem to understand research as a rather single-faceted phenomenon, object-oriented and collections-based. If codes of ethics are the epitome of museum professionalism and museum values, then these ethics should be embodied in new provisions for museum research. Notions like social inclusion, public accountability, and transparency, are central in museum research, and should be included in all codes of ethics as well, reflecting the efforts museums make to embody democratic ideals and share both research and writing of history with their audience, thus creating communities of knowledge. This paper aims to contribute to the debate on museum codes of ethics and to provide some ideas for future revisions.